Optimal allocation of a cross-connection and sectionalizers in distribution systems - Ziari, I.; Ledwich, G.; Wishart, M.; Ghosh, Arindam; Dewadasa, M. (Institute of Electrical and Electronics Engineers ( IEEE ), 2010)
This paper compares the performance of two droop control schemes in a hybrid microgrid. With presence of both converter interfaced and inertial sources, the droop controller share power in a decentralized fashion. Both the droop controllers facilitate reactive power sharing based on voltage droop. However in frequency droop control, the real power sharing depends on the frequency, while in angle droop control, it depends on output voltage angle. For converter interfaced sources this reference voltage is tracked while for inertial DG, reference power for the prime mover is calculated from the reference angle with the proposed angle control scheme. This coordinated control scheme shows significant improvement in system performance. The comparison with the conventional frequency droop shows that the angle control scheme shares power with much lower frequency deviation. This is a significant improvement particularly in a frequent load changing scenario.